1992
DOI: 10.1128/jb.174.19.6264-6269.1992
|View full text |Cite
|
Sign up to set email alerts
|

New mutations in and around the L2 disordered loop of the RecA protein modulate recombination and/or coprotease activity

Abstract: The RecA protein plays a key role in Escherichia coli recombination and DNA repair. We have created new recA mutants with mutations in the vicinity of the recA430 mutation which is known to affect RecA coprotease activity. Mutants carrying recA659 or recA611, located 3 and 7 amino acids downstream of residue 204, respectively, lose all RecA activities, while the mutant carrying recA616, which is located at 12 amino acids from this residue, keeps the coprotease activity but is unable to promote recombination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Consequently, we assessed whether homologous recombination is necessary for production of CTX virions by strains with tandem prophages, using two recA Ϫ derivatives of BD81. One derivative, BD206, has a 2.8-kb deletion encompassing most of recA whereas the other, BD578, has a point mutation (K215Q) expected to impair homologous recombination but not RecA-mediated protease activity (16). We found that supernatants from BD206 yielded significantly fewer transductants than the isogenic wild type strain, although Kn R colonies were still obtained with an average frequency of 420 transductants ϫ OD 600 Ϫ1 ϫ ml Ϫ1 (Fig.…”
Section: Production Of Ctx From Prophage Arrays Does Not Depend Onmentioning
confidence: 83%
“…Consequently, we assessed whether homologous recombination is necessary for production of CTX virions by strains with tandem prophages, using two recA Ϫ derivatives of BD81. One derivative, BD206, has a 2.8-kb deletion encompassing most of recA whereas the other, BD578, has a point mutation (K215Q) expected to impair homologous recombination but not RecA-mediated protease activity (16). We found that supernatants from BD206 yielded significantly fewer transductants than the isogenic wild type strain, although Kn R colonies were still obtained with an average frequency of 420 transductants ϫ OD 600 Ϫ1 ϫ ml Ϫ1 (Fig.…”
Section: Production Of Ctx From Prophage Arrays Does Not Depend Onmentioning
confidence: 83%
“…Upon AgeI digestion, the amplified DNA fragment was cloned into the large fragment of AgeIdigested pCCrecA to give pCCE207K recombinant plasmid. recA E207Q (14,20) was cloned in the same vector.…”
Section: Methodsmentioning
confidence: 99%
“…SOS induction was measured using a bacterial strain carrying a cea::lacZ fusion and measuring ␤-galactosidase expression as described elsewhere (14,15). The induction factor is the ratio of ␤-galactosidase activities after and before irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations